Generative AI in Studio-Based Fashion Education: A Systematic Literature Review - Anwar, Rabia; Raza, Fahd Ali; Marzouk, Mostafa El-Sayed (Electronic Journal of Business and Management, 2025)
This systematic literature review explores the integration of generative artificial intelligence (GenAI) into studio-based fashion education between 2018 and 2025. Drawing from 28 academic sources across design, architecture, and education, the review synthesizes current knowledge on how GenAI influences key pedagogical dimensions within the studio model. Four core thematic pillars emerge: Knowledge Construction, Learner Identity & Authorship, Teaching Practice, and Studio Culture & Ethics. These themes reveal both the opportunities and tensions presented by GenAI, ranging from enhanced creative ideation and efficiency to concerns over originality, ethical responsibility, and equitable access. To guide implementation, the paper proposes the Simplified GAI–SBL Model, a conceptual framework aligning GenAI use with established pedagogical values and design practices. This model serves as a foundation for future empirical validation and practical adaptation in curriculum design. The review highlights the need for deliberate integration strategies that preserve studio culture while embracing technological innovation. By balancing innovation with ethical and educational rigor, the field can shape a future where GenAI enhances, rather than displaces, the core objectives of fashion design education.